SISTEM INFORMASI MANAJEMEN LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS ISLAM KALIMANTAN MAB BANJARMASIN - Rahmadi Agus; Rizqi Elmuna Hidayah; Muhammad Edya Rosadi (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
The long-term goal of this research is to improve the research performance of Research Institute and Pegabdian to the Society of Islamic University of Borneo Muhammad Arsyad Al-Banjari specifically to the Institutional Information System which must be improved from time to time continuously following developments especially in the submission of program proposals by the Directorate Research and Community Service (DRPM) Directorate General of Research and Development Strengthening. Target to be achieved is to make an application that can map data result of research performance of lecturer of UNISKA MAB Banjarmasin using Waterfall method also documentation of system development become very organized, where every step must be completed perfectly before stepping to next stage. It is expected that with this method the Information System made will be good and in accordance with the objectives of the study so that there is no repetition in the title proposal and implementers in accordance with the requirements that have been determined and support in the completeness of Lecturer such as for Lecturer Workload, Employee Work Objectives, easier lecturer certification accessed in existing data retrieval. It is expected that this system can be a problem solver that occurs at the Research and Pegabdian Institute to the Society of Islamic University of Borneo Muhammad Arsyad Al-Banjari. Keywords:       waterfall method, management information system, research performance, data mapping, information system